Loquat-tea intercropping enhances rhizosphere microbial diversity and functional profiles in tea soil ecosystems - Zou, Chengyi; Dai, Tianfei; Liang, Zhonghua; Li, Mingyan; Meng, Lina; Zhao, Xianming; Li, Nianzhen; Wei, Qin; Abd Elhamid, Mohamed A.; Atif, Amr M.; Soaud, Salma A.; Wen, Mengling; et al. (Frontiers in Microbiology, 2025)
IntroductionIntercropping systems can significantly influence soil microbial communities, affecting plant health and soil nutrient cycling, which has better economic and ecological benefits than monoculture of tea.MethodsThis study investigated the impact of loquat-tea intercropping on the microbial community structure and functional gene composition in the rhizosphere soil of tea (Camellia sinensis). Using metagenomic sequencing, we analyzed rhizosphere soils from loquat-tea intercropping (PP_CS), tea monoculture (CS), and loquat monoculture (PP).Results and discussionA total of 161 phyla, 269 classes, 485 orders, 1,000 families, 3,838 genera, and 27,624 species were annotated across samples. Dominant phyla included Actinobacteria, Proteobacteria, Acidobacteria, and Chloroflexi. The genera Bradyrhizobium (4.20%) and Trebonia (3.78%) were notably enriched in the intercropping system. The analysis of community differences showed that unclassified_c_acidobacteria was in pp_cs group, demonstrating the highest LDA score (4.4 score). Functional annotation via the Kyoto Encyclopedia of Genes and Genomes (KEGG) revealed that metabolic pathways were predominant across all treatments, with 36,111,608 reads assigned to metabolism. The comparative analysis at KEGG level 3 revealed that Metabolic pathways 289 constituted the most abundantly annotated functional category across all three groups. Redundancy analysis (RDA) showed strong correlations between key microbial genera (Trebonia, Bradyrhizobium) and soil properties, including organic matter (OM), alkali hydrolyzed nitrogen (AN), available phosphorus (AP), and available potassium (AK). These findings suggest that loquat-tea intercropping promotes microbial diversity and enhances functional potential, improving soil health and nutrient availability in tea cultivation systems.